Pacing device for swimming: Mechanical construction of constant speed - Messinis, S.; Platanou, T. (Journal of Physical Education and Sport, 2010)
The pace in swimming is very important because it allows swimmers to allocate their forces accordingly, and therefore a distance to travel as quickly as possible. The training pace at different swimming speeds and combinations thereof, is an important part of training before the competitions. The definition and maintenance of the stable and swimmer specific speed is difficult to achieve and requires considerable effort and experience. To determine the desired rate of accuracy by the researchers and their coaches used till now, various audio and visual media. However, some of these institutions did not very accurately measure the rate and not all styles of swimming, while other aspects affect the proper swimming. In this construction, a key objective is to solve the problems occurring in the previous constructions, the modern technological development of them and the adaption of the specificities of different swimming styles. This device consists of an electro 3 / 8 of the horse, a flange, a single inverter from 3 / 8 to ½ of the horse, pulleys with taper Bush, flange axle, pulleys, platforms and a 52 meters cable. The assembly and operation is as follows: At the edge of the pool next to the platform is placed the base of pulleys, the electro set is connected to the inverter and the axle flange. Precisely opposite is positioned the other base. Along the pool «moves» the cable that connects the two bases, located 150 cm above the water. A fixed point on the cable is marked with paint in order to be visible to the swimmer during backstroke swimming while for other styles we adapt a lamination at the cable vertically in the pool, above the surface a sheet of 15 cm which is painted with strong color that is visible from the athlete and will precede him. Setting the speed with inverter it starts from one end of the tank leading to the other, doing a circular motion. The swimmer is required to follow the marked point of the cable in the backstroke or lamination in other styles. Practical applications of the use of speed regulator: 1) Determination of constant speed (rate) of the athlete, without movement problems 2) Growth rate of change in perception of the athlete. 3) Verification of proper technique 4) Training in the change of pace, planning and competition tactics.